Summary of Speeches at the Opening of Legal Year 2015 - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2015)
The Opening of the Legal Year the Legal Year 2015 saw the usual three speeches by the Attorney-General, the President of the Law Society, and the Chief Justice. But perhaps the only thing usual was the fact that three speeches were made; indeed, on the 50th anniversary of Singapore’s national independence, the speeches were not of the usual mould. Instead, they were contemplative of the lessons drawn from the past, consolidating of the progress made in the present, and boldly hopeful in propelling the Singapore legal system to meet the new challenges of the next 50 years. This entry aims only to summarise these three key speeches for the benefit of readers who may not wish to read them in their entirety.